2017
DOI: 10.1186/s12969-017-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

BK viruria and viremia in children with systemic lupus erythematosus

Abstract: BackgroundBK virus (BKV) is a ubiquitous polyoma virus that lies dormant in the genitourinary tract once acquired in early childhood. In states of cellular immunodeficiency, the virus can reactivate to cause hemorrhagic cystitis and nephritis. Children with systemic lupus erythematosus (SLE) have an increased risk of developing infectious complications secondary to their immunocompromised state from the administration of several immuno-modulatory drugs. Currently, there are no data regarding the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…EBV promotes B cell proliferation, and some of the encoded proteins, such as nuclear antigen 1 (EBVN-1), share sequence homology with SLE autoantigens and may induce via antigenic mimicry antibodies that crossreact with the ribonucleoproteins (RNPs) Ro, Sm B/B’ and Sm D1 [ 20 ]. Besides EBV, tentative associations with SLE have been reported for parvovirus B19 [ 21 ], cytomegalovirus [ 22 ], and polyomavirus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…EBV promotes B cell proliferation, and some of the encoded proteins, such as nuclear antigen 1 (EBVN-1), share sequence homology with SLE autoantigens and may induce via antigenic mimicry antibodies that crossreact with the ribonucleoproteins (RNPs) Ro, Sm B/B’ and Sm D1 [ 20 ]. Besides EBV, tentative associations with SLE have been reported for parvovirus B19 [ 21 ], cytomegalovirus [ 22 ], and polyomavirus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colla et al reported increased BKPyV viruria in adult SLE, and they also reported an association between proteinuria and BKPyV viruria [30]. SLE patients are believed to be at risk of developing infectious complications due to their suppressed immune systems caused by various immunomodulatory drugs [31]. In addition, it has been speculated that there is a relationship between BKPyV reactivation and anti-dsDNA antibody production [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…6 Patients with autoimmune diseases, such as SLE, by themselves immunosuppressant, have been found to have higher rates of BKV viremia and viruria. 4,7…”
Section: Discussionmentioning
confidence: 99%